Ruthenium(iv) N-confused porphyrin μ-oxo-bridged dimers: acid-responsive molecular rotors. Issue 40 (13th July 2021) - Iwanaga, Osamu; Fukuyama, Kazuki; Mori, Shigeki; Song, Jun Tae; Ishihara, Tatsumi; Miyazaki, Takaaki; Ishida, Masatoshi; Furuta, Hiroyuki
Abstract : Ring rotation of ruthenium(iv ) N-confused porphyrin μ-oxo-dimer was controlled by protonation at the peripheral nitrogen moieties. Abstract : Ruthenium(iv ) N-confused porphyrin μ-oxo-bridged complexes were synthesized via oxidative dimerization of a ruthenium(ii ) N-confused porphyrin complex using 2, 2, 6, 6-tetramethylpiperidine 1-oxyl. The deformed core planes in the dimers conferred a relatively high ring rotational barrier of ca. 16 kcal mol −1 . Rotation of the complexes was controlled by protonating the peripheral nitrogen.